Clinically relevant cranio-caudal patterns of cervical cord atrophy evolution in MS. (12th November 2019) - Rocca, Maria A.; Valsasina, Paola; Meani, Alessandro; Gobbi, Claudio; Zecca, Chiara; Rovira, Àlex; Montalban, Xavier; Kearney, Hugh; Ciccarelli, Olga; Matthews, Lucy; Palace, Jacqueline; Gallo, Antonio; et al.
Abstract : Objective: To characterize the distribution and regional evolution of cervical cord atrophy in patients with multiple sclerosis (MS) in a multicenter dataset. Methods: MRI and clinical evaluations were acquired from 179 controls and 435 patients (35 clinically isolated syndromes [CIS], 259 relapsing-remitting multiple sclerosis [RRMS], 99 secondary progressive multiple sclerosis [SPMS], and 42 primary progressive multiple sclerosis [PPMS]). Sixty-nine controls and 178 patients underwent a 1-year MRI and clinical follow-up. Patients were classified as clinically stable/worsened according to their disability change. Longitudinal changes of cord atrophy were investigated with linear mixed-effect models. Sample size calculations were performed using age-, sex- and site-adjusted annualized percentage normalized cord cross-sectional area (CSAn) changes. Results: Baseline CSAn was lower in patients with MS vs controls ( p < 0.001), but not different between controls and patients with CIS or between patients with early RRMS (disease duration ⩽5 years) and patients with CIS. Patients with late RRMS (disease duration >5 years) showed significant cord atrophy vs patients with early RRMS ( p = 0.02). Patients with progressive MS had decreased CSAn ( p < 0.001) vs patients with RRMS. Atrophy was located between C1/C2 and C5 in patients with RRMS vs patients with CIS, and widespread along the cord in patients with progressive MS vs patients with RRMS, with an additional C5/C6 involvement in patients with SPMS vs patients with PPMS. At follow-up, CSAn decreased in all phenotypes ( p < 0.001), except CIS. Cord atrophy rates were highest in patients with early RRMS and clinically worsened patients, who had a more widespread cord involvement than stable patients. The sample size per arm required to detect a 50% treatment effect was 118 for patients with early RRMS. Conclusions: Cord atrophy increased in MS during 1 year, except for CIS. Faster atrophy contributed to explain clinical worsening.